Impact of malignancy on clinical outcomes in patients with acute coronary syndromes. (1st April 2021) - Yousif, Nooraldaem; Niederseer, David; Davies, Allan; El Issa, Meidi; Sidia, Besma; Noor, Husam A.; Amin, Haitham; Räber, Lorenz; Gencer, Baris; Klingenberg, Roland; Windecker, Stephan; Mach, François; et al.
Abstract: Background: The impact of cancer on survival in patients with coronary artery disease has not been well defined. We designed the present study to explore the prevalence and prognostic influence of cancer in patients with acute coronary syndrome (ACS). Methods: 2′132 patients with ACS were enrolled in the prospective, multicenter Special Program University Medicine ACS (SPUM-ACS) cohort. The primary endpoints of major cardiovascular and cerebrovascular events (MACCE) and death were independently adjudicated at 30-day and at one-year follow-up. Results: Of the 2′132 ACS patients 7.74% ( n = 165) had cancer. At 30-day, except for net adverse clinical events (NACE defined as MACCE plus major bleeding), outcomes did not differ significantly between the two groups. At one year, MACCE rate was higher in cancer than in non-cancer patients (21.8 vs. 12.2%, p < 0.001). Even after adjusting for covariates, one-year all-cause mortality was higher in cancer patients than in those without (30.3% vs. 11.9%; p < 0.0001) as was cardiovascular mortality (15.7% vs. 5.9%; p < 0.001) and revascularization (12.7% vs. 5.5%, p < 0.001). Net adverse clinical events were also higher in patients with cancer at one-year follow-up (33.9% vs. 19.8%, p < 0.001). A sub-analysis revealed that those with solid tumors, but not hematological malignancies were more likely to experience MACCE ( p = 0.001) as well as a higher cardiovascular and all cause mortality (both p = 0.001) at one-year follow-up. Conclusions: ACS patients with cancer, specifically those with solid tumors, have a higher MACCE as well as cardiovascular and total mortality rate than non-cancer patients independent of cardiovascular risk factors. Thus, cancer is an independent risk factor for a poor outcome in ACS patients. Highlights: Cancer is a novel cardiovascular risk factor in its own right. Cancer should be implemented in acute coronary syndrome (ACS) risk scores. Closer monitoring of cancer patients with ACS by a cardio-oncology team is crucial.